USE OF COMPUTATIONAL MODELING TO SIMULATE THE DRIFT OF STRANDING CETACEANS IN COASTAL REGIONS. A CASE STUDY IN THE PAULISTA COASTLINE - Lugon Jr., Jader; Kalas, Francine de Almeida; Rodrigues, Pedro Paulo Gomes Watts; Juliano, Maria Manuela; Gallo Neto, Hugo; Jeveaux, José Luiz; Silva Neto, Antônio José (REVISTA CEREUS, 2019)
In this work it is simulated the trajectory of a beached whale sighted near Ilhabela region, in Sao Paulo coastline, Brazil, in November, 2017. The computational implementation was performed on the MOHID platform (Hydrodynamic Model), using Water module. The downscaling technique was used to obtain local hydrodynamic currents at local scale. The validity of the model was considered satisfactory after statistical analysis comparing the results to satellite measurements of the sea surface temperature and also temperature and salinity profiles measured by ARGO buoys, attesting the purpose to use the model to simulate the trajectory of the cetacean specimen. The use of these technologies has great potential for researchers, since it allows the accompaniment of these organisms and avoids the stranding in tourist or densely populated regions, like the Paulista region.